The Mediating Role of Emotional Intelligence in the Organisational Commitment and Turnover Intention of Clinical Nurses: A Cross‐Sectional Study - Han Lingyu; Li Ruiling; Wang Yiman; Liu Yafeng; Bai Xiaolu (Nursing Open, 2025)
ABSTRACT Aim To explore the influence of emotional intelligence and organisational commitment (OC) on clinical nurses' turnover intention (TI) and to provide intervention strategies to reduce the turnover rate of nursing staff and maintain the stability of the nursing team. Design A cross‐sectional descriptive study was conducted with nurses (n = 452) in a tertiary hospital in Kaifeng City, Henan Province, China. Methods The project was conducted in July 2023. The data were collected using the organisational commitment scale, Wong and Law emotional intelligence scale and turnover intention scale. Results The emotional intelligence score of clinical nurses was (3.07 ± 0.68), organisational commitment scale was (3.04 ± 0.68), and turnover intention scale was (2.70 ± 0.58). Organisational commitment scale and emotional intelligence scores are negatively correlated with turnover intention; the mediating effect of emotional intelligence in organisational commitment and turnover intention scale of clinical nurses is −0.406, and the mediating effect accounts for 49.9%. Public Contribution Nurses' organisational commitment can directly predict turnover intention, and emotional intelligence plays a role in mediating the relationship between nurses' organisational commitment and turnover intention. This research makes a substantial contribution to the public and healthcare sector. The findings provide valuable insights for healthcare administrators, policy‐makers and educators, offering evidence‐based strategies to improve nurse retention and enhance the quality of patient care. It is important to note that the research upholds the highest standards of integrity, with a meticulous review process and a dedicated effort to maintain data quality.